2009
DOI: 10.1111/j.1440-1746.2008.05651.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of patients with gastric variceal hemorrhage: Endoscopic N‐butyl‐2‐cyanoacrylate injection versus balloon‐occluded retrograde transvenous obliteration

Abstract: The therapeutic efficacies of EBC and BRTO for the treatment of active GVH and/or high-risk GV appeared to be similar. However, EBC might be associated with a higher rebleeding rate than BRTO. BRTO could be an effective rescue treatment for patients with GVH after initial treatment of EBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 29 publications
3
119
1
2
Order By: Relevance
“…[8][9][10][11] Its use is gradually increasing in other countries such as the United States, [12][13][14] where transjugular intrahepatic portosystemic shunt (TIPS) placement is currently the standard treatment for GVs. 15 The reported rate of GV rebleeding is significantly lower after B-RTO than after TIPS placement 16 or endoscopic intervention, 17 but B-RTO results in increased portal venous pressure (PVP), which may cause enlargement of EVs. 18,19 We previously reported on the efficacy and safety of simultaneous combined B-RTO and partial splenic embolization (PSE) for GVs 20 based on the hypothesis that concomitant PSE can diminish the increase in PVP after B-RTO.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Its use is gradually increasing in other countries such as the United States, [12][13][14] where transjugular intrahepatic portosystemic shunt (TIPS) placement is currently the standard treatment for GVs. 15 The reported rate of GV rebleeding is significantly lower after B-RTO than after TIPS placement 16 or endoscopic intervention, 17 but B-RTO results in increased portal venous pressure (PVP), which may cause enlargement of EVs. 18,19 We previously reported on the efficacy and safety of simultaneous combined B-RTO and partial splenic embolization (PSE) for GVs 20 based on the hypothesis that concomitant PSE can diminish the increase in PVP after B-RTO.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that B-RTO was a safe and effective procedure for the treatment of fundal GV, as eradication of the varices was confirmed in 31 of 32 patients without serious side effects [136]. Hong et al [137] reported that EIS with cyanoacrylate was associated with a higher rebleeding rate than B-RTO, although the immediate efficacies of these two treatments for bleeding GV and high-risk GV were similar. Akahoshi et al [138] reported that B-RTO was superior to EIS with cyanoacrylate and ethanolamine oleate in preventing rebleeding from isolated fundal GV with a major shunt.…”
Section: Antifibrotic Therapymentioning
confidence: 99%
“…Another prospective multicenter randomized controlled clinical trial enrolled 140 patients with Child-Pugh class A and B cirrhosis and refractory variceal bleeding and randomized them to undergo DSRS (73) or TIPS (67) [78]. After a mean follow-up of 46 months there was no significant difference in rebleeding (DSRS, 5.5%; TIPS, 10.5%; P=0.29) or first encephalopathy event (DSRS, 50%; TIPS, 50%).…”
Section: Surgical Portosystemic Shunts Versus Tipsmentioning
confidence: 99%
“…TIPS has been found to be quite effective in the prevention of GV rebleeding, not only by reducing the portal pressure but also by allowing the possibility of transhepatic obliteration of gastric variceal channels [72]. A number of radiologic or combination endoscopic-radiologic techniques such as BORTO (balloon-occluded retrograde transvenous obliteration and percutaneous transhepatic obliteration) and balloon-occluded endoscopic injection sclerotherapy have been pioneered in Japan, but need further evaluation [73].…”
Section: Management Of Gastric Variceal Bleedingmentioning
confidence: 99%